Ancestral and local adaptation contribute to dispersal out of the Qinghai–Tibet Plateau in a bumblebee - Chunyan Jiang; Lei Yue; Dacheng Jin; Ruting Zou; Yu Wang; Biao Li; Xuexiao Du; Xianliang Huang; Yingmin Sun; Renze Wang; Jiandong An; Lijun Cao; et al. (Proceedings of the National Academy of Sciences, 2026)
The Qinghai–Tibet Plateau (QTP) region is the greatest hotspot of social bumblebee diversity worldwide. However, how the high diversity of bumblebees in the QTP evolved and contributed to their diversification in adjacent and far-reaching regions remains unclear. Here, we explored this question using a widespread bumblebee species, Bombus pyrosoma . Phylogenomic analysis revealed a history of dispersal out of the QTP and distinct lineage divergence along elevations within the species. Four major chromosomal inversion variants were identified, and shifts in their frequency with altitude were consistent with patterns of lineage divergence. The highland bumblebees showed stronger metabolic robustness and better flight performance under cold environments, whereas lowland ones excelled under warm conditions. Forty-one percent of the positively selected genes were located in the inversion regions and were mostly associated with fatty acid metabolism and information processing. Mutation with a strong candidate gene, elovl6 , possibly modulated long-chain fatty acid elongation, which facilitated bumblebee flight under thermal stress. Finally, genomic inversion analyses across 22 bumblebee species–17 native to the QTP–corroborate the widespread involvement of inversions in the elevational diversification of bumblebees. Overall, our findings revealed that chromosomal inversions play a pivotal role in facilitating local adaptation and dispersal out of the QTP in a bumblebee, providing insights into the genomic underpinnings of bumblebees’ diversification.